REPRESENTASI MASKULINITAS PADA KARAKTER PEREMPUAN DI FILM THE 355 (2022) - Bella Charina Putri; Muhammad Bayu Widagdo (Interaksi Online, 2026)
Films can construct gender roles in society by conveying them through their characters. The film "The 355 (2022) depicts characters with masculine traits: tough, physically strong, intelligent, and independent of men. Based on this context, this study aims to analyze the representation of female masculinity in the film The 355 (2022). This study uses representation theory as the primary theory, supplemented by elements of masculinity as outlined by Peter Lehmann, traits as outlined by Meehan, and Judith Halberstam's theory of masculinity. The analytical method employed is Roland Barthes's semiotic analysis, with three levels of coding: denotation, connotation (with five reading codes), and myth. Overall, the masculinity that appears in the film The 355 in female characters is characterized by the presence of things that are understood by society as "masculine" by showing scenes that contain visual and verbal symbols that are constructed in nature, attitudes, responses, and reactions that contain elements of power, courage, heroism, and leadership and have dominant, independent, rational, assertive, analytical, brave, active, and insensitive characteristics. The formation of masculinity is also influenced by the experiences of each character in facing differences in power relations in organizations and societies that adhere to patriarchal ideology. The film The 355 also seems to try to deconstruct the myth that women are subordinate and present a counter ideology, namely feminist ideology, especially liberal feminism.